Multimodal gadolinium oxysulfide nanoparticles for bioimaging: A comprehensive biodistribution, elimination and toxicological study. (May 2020) - Santelli, Julien; Lechevallier, Séverine; Calise, Denis; Marsal, Dimitri; Siegfried, Aurore; Vincent, Marine; Martinez, Cyril; Cussac, Daniel; Mauricot, Robert; Verelst, Marc
Abstract: For some years now, gadolinium oxysulfide nanoparticles (NPs) appear as strong candidates for very efficient multimodal in vivo imaging by: 1) Magnetic Resonance (MRI), 2) X-ray Computed Tomography (CT) and 3) photoluminescence imaging. In this paper, we present a selection of results centered on the evaluation of physico-chemical stability, toxicity, bio-distribution and excretion mechanisms of Gd2 O2 S:Ln 3+ nanoparticles intravenously injected in rats. Two formulations are here tested with a common matrix and different dopants: Gd2 O2 S:Eu 3+ 5% and Gd2 O2 S:Yb 3+ 4% /Tm 3+ 0.1% . The NPs appear to be almost insoluble in pure water and human plasma but corrosion/degradation phenomenon appears in acidic conditions classically encountered in cell lysosomes. Whole body in vivo distribution, excretion and toxicity evaluation revealed a high tolerance of nanoparticles with a long-lasting imaging signal associated with a slow hepatobiliary clearance and very weak urinary excretion. The results show that the majority of the injected product (>60%) has been excreted through the feces after five months. Experiments have evidenced that the NPs mainly accumulate in macrophage-rich organs, that is mainly liver and spleen and to a lesser extent lungs and bones (mainly marrow). No significant amounts have been detected in other organs such as heart, kidneys, brain, intestine and skin. Gd2 O2 S:Ln 3+ NPs appeared to be very well tolerated up to 400 mg/kg when administered intravenously. Statement of Significance: Since 2011, we have focused our work on Gd2 O2 S nanoparticles (NPs) for multimodal bioimaging using fluorescence, Magnetic Resonance Imaging (MRI) and Computed Tomography with very efficient results already published. However, since the European Medicines Agency has concluded its review of gadolinium contrast agents, confirming recommendations to restrict the use of some linear gadolinium agents used in MRI, a particular attention must be paid to any new contrast media containing gadolinium. Therefore, we present in this paper a compilation of studies about toxicity, bio-distribution and excretion mechanisms of Gd2 O2 S:Ln 3+ NPs intravenously injected into rats. We also present an in vitro kinetic study of NPs degradation in aqueous and biological media to provide some information on chemical and biological stability. Graphical abstract: Image, graphical abstract